The Role of Agricultural Innovation in Enhancing Food Security in Sub-Saharan Africa - Kimani, Sarah (International Journal of Developing Country Studies, 2024)
Purpose: The general objective of the study was to investigate the role of agricultural innovation in enhancing food security in Sub Saharan Africa. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the role of agricultural innovation in enhancing food security in Sub Saharan Africa. Preliminary empirical review revealed that agricultural innovation was critical in addressing the pervasive food insecurity in Sub-Saharan Africa. It found that innovations in crop breeding, sustainable farming practices, precision agriculture, and improved agricultural inputs significantly increased productivity and food availability. However, the study emphasized that these innovations needed to be context-specific due to the diverse agro-ecological and socio-economic conditions in the region. Additionally, barriers such as limited access to finance, inadequate extension services, and poor infrastructure were identified as significant obstacles to the adoption of agricultural innovations. The study also highlighted the importance of integrating sustainability and resilience into agricultural practices to ensure long-term food security. Unique Contribution to Theory, Practice and Policy: Diffusion of Innovations Theory, Sustainable Livelihoods Framework and Innovation Systems Theory may be used to anchor future studies on food security in Sub Saharan Africa. The study recommended further research into the contextual factors influencing the adoption and impact of agricultural innovations, suggesting that more region-specific studies could provide deeper insights. It also emphasized strengthening agricultural extension services and leveraging digital technologies to enhance farmers' access to information. Improving financial access for smallholder farmers through tailored credit products and public-private partnerships was also advised. On the policy front, the study called for supportive policies that reduce regulatory barriers and promote sustainable practices. Additionally, fostering collaboration among stakeholders and enhancing capacity-building initiatives were recommended to empower farmers and facilitate the widespread adoption of agricultural innovations.